Effect Of Zinc And Ingredients Of Protein Supplement On Sperm Parameters And Male Reproductive Hormones- An RCT Study - Saira Safdar; Irfan Afzal Mughal; Noor Ul Ain; Sidra Jabeen; Muhammad Hassaan Farooq; Asma Irfan (Journal of Rawalpindi Medical College)
Objective: The purpose of this study was to assess the protective effects of zinc against injury to sperm parameters and male reproductive hormones brought on by toxic protein supplement constituents.